A Study Of The Relationship Between Green Governance And Sustainable Finance In PSU Banks (International Journal of Food and Nutritional Sciences, 2022)
In order to strengthen its green infrastructure, achieve its sustainable development goals, and address climate concerns like global warming, its enormous population, and enormous green depletion, India must now accept challenges from the international community. Green finance must be used if the nation is to survive. Green finance, often known as climate finance, requires a shift in emphasis and behavior from conventional forms of funding to more environmentally friendly financing. India needs a green finance plan if it is to meet its lofty objectives for sustainable development. It is necessary to persuade Indian, as well as global, financial institutions and corporations, to refocus on the topic of green finance. There have been many opportunities and difficulties on this front. In order to manage India's sustainable development objectives and go forward with green financing, this study aims to comprehend the scenario in which India currently finds itself. This study is descriptive in nature and is based on secondary data referred from government, national, and international institutions.